AB0722 Ominous Prognosis of Secondary Amyloidosis in Patients with Spondyloarthropathies. (10th June 2014) - Rodríguez-Muguruza, S.; Martinez-Morillo, M.; Holgado, S.; Riveros-Frutos, A.; Sanint, J.; Prior, A.; Mateo, L.; Cañellas, J.; Tena, X.; Olive, A.
Abstract : Background: Secondary amyloidosis (AAa) is a disorder caused by deposition of insoluble amyloid A fibrils in different tissues and organs. It is a rare and serious complication of rheumatic diseases including spondyloarthropathies. Objectives: The aim of this study was to determine the clinical features, laboratory data, treatment and clinical outcome of patients with spondyloarthropathies who developed AAa. Methods: Design retrospective (1984-2013). Hospital: academic tertiary hospital. Referral area: 850.000 inhabitants. We reviewed the medical records of 1125 patients with spondyloarthropathies: 509 (45%) psoriatic arthritis (PsA), 263 (23%) ankylosing spondylitis (AS), 128 (11.3%) spondylitis associated with inflammatory bowel diseases (IBD), 190 (16.8%) undifferentiated spondyloarthropathy and 35 (3.1%) reactive arthritis diagnosed at our centre. We selected patients who had a histological diagnosis of AAa. Results: Twelve (1.06%) patients with AAa were recruited: 10 (83%) males and 2 (16.6%) females. Five (41, 6%) AS, 3 (25%) PsA, 3 (25%) spondylitis associated with IBD and 1 (8%) reactive arthritis. Mean age at AAa diagnosis: 55.75 years (interval 71-33 years). Amyloid deposits were observed on rectal biopsy (5 cases), kidney biopsy (3 cases) and subcutaneous fat biopsy (2 cases). In two cases the diagnosis was made incidentally (bladder and gallbladder). The mean age at spondyloarthropathy diagnosis was 32 years and the mean disease duration was 23.2 years. The mean values of erythrocyte sedimentation rate and C-reactive protein, at diagnosis of AAa, were 58.71mm and 35.47 mg/L respectively. AAa was suspected in 8 patients because of nephrotic-range proteinuria (2 patients), acute renal failure (5 patients) and diarrhea (1 patient). HLA B27 was positive in 6 patients, negative in 2. Five patients were treated with infliximab, 4 of whom because amyloidosis. Four patients underwent hemodialysis for end-stage renal disease, one of them died because complications directly related to renal failure. Four patients died of sepsis. Conclusions: The frequency of clinical apparent AAa in our patients was 1.06% (12 patients). There was a marked male predominance. Clinical AAa was diagnosed at a relatively late stage in spondyloarthropathies. The predominant clinical picture was nephrotic syndrome. Prognosis was ominous. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3143